Характеристика окремих аспектів причетності до злочину - Гусак, А.; Husak, A. (Східноєвропейський національний університет ім. Лесі Українки, 2015)
У статті розглядаються склади злочинів, присвячені прихованню, які є видами причетності до злочину. На думку автора причетність до злочину – це навмисна діяльність осіб, які не брали участь у злочині, спрямована на приховування вже вчиненого злочину, а також умисна бездіяльність осіб, зобов'язаних відповідно до чинного законодавства діяти. Інститут приховування злочину містить норми, які необхідно удосконалювати. Перелік діянь, зазначених у Кримінальному кодексі України, як приховування, слід доповнити такими способами, як заздалегідь не обіцяне переховування, приховування, пошкодження або знищення доказів злочину, заздалегідь необіцяна допомога учаснику злочину отримати вигоду від вчиненого без власної корисливої мети. The article considers offenses dealing with concealing (corpus delicti), and which are classified as types of complicity in the crime. The author states that institute of concealing the crime includes the regulations that need to be improved. It is recommended to supplement the list of the acts referred to in the Criminal сode of Ukraine with such types of concealing as not promised beforehand hiding; damage or destruction of evidence of a crime; not promised to the participant of a crime beforehand aid to benefit from the offense without one’s own selfish purpose. The main aim of the article is to present the notion complicity in modern understanding and interpretation. Criminal involvement – is an intention of persons, who do not commit crimes but want to conceal the committed crime, and lack of actions on behalf the persons who must act according to modern Criminal сode. But at the same time such passive actions of these people cannot be punished according to the modern Criminal сode. Key words: concealing, hiding, involvment, complicity, crime.
Different Aspects of Criminal Involvment.
Keywords: приховання; укриття; причетність; співучасть; злочин; concealing; hiding; involvment; complicity; crime